THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Ibragimova Hilola Bahodirjon qizi (Bright Mind Publishing, 2026)
This article explores the integration of artificial intelligence (AI) technologies into the education system, highlighting their advantages, opportunities, and emerging challenges. The paper analyzes the role of AI in personalizing the learning process, enabling adaptive learning, and creating interactive and immersive educational environments. Particular attention is given to modern AI-based tools such as Magic School AI, Eduaide AI, Diffit.me, Curipod, Brisk Teaching, and Kialo Edu, which support lesson planning, assessment, feedback, and communication. The study also identifies key challenges in implementing AI in education, including digital inequality, data privacy, technological accessibility, and algorithmic bias. The importance of ethical principles, transparency, and accountability in the use of AI technologies is emphasized. The conclusion suggests that responsible and equitable application of AI can enhance quality, equity, and inclusivity in education.
Keywords: Artificial intelligence, education system, digital divide, ethical issues, transparency, adaptive learning, Magic School AI, Edu aide AI, interactive learning, data security.